The Effects of Glutathione Monoethyl Ester on Different Biochemical, Oxidant, and Antioxidant Levels During Storage in Leukoreduced Red Blood Cells - Behrooz Ghezelbash; Mohammadreza Deyhim; Azita Azarkeivan; Ali Akbar Pourfathollah; Nahid Eskandari (Advanced Biomedical Research)
Background: It is essential to maintain the quality of the stored blood, because various factors affect the stored red blood cells (RBCs) over time, some red blood cell storage lesions (RCSL) develop during storage, and it could reduce the function of the RBCs. The present study aimed to evaluate the effects of glutathione monoethyl ester on different biochemical changes, oxidant, and antioxidant levels in the leukoreduced RBCs (LR-RBCs) during storage. Materials and Methods: About 10 units of LR-RBC were collected, processed and stored according to the standard operating procedures (SOPs) of the Iranian Blood Transfusion Organization. Each unit divided into 2 equal parts; LR-RBC treated with glutathione monoethyl ester and a control group. Exposure of phosphatidylserine (PS), reactive oxygen species (ROS) and microvesicle derived from the RBCs (RBC-MVs), were measured by the flow cytometry method. ELISA was used to measure the level of glutathione, and 2, 3-diphosphoglycerate (2,3-DPG). Glucose-6-phosphate dehydrogenase (G6PD) enzyme activity was measured with a chemistry autoanalyzer. Results: The levels of glutathione reduced the initial value in the treated group (80%), and the control group (60%), respectively. Exposure of surface PS, ROS and RBC-MVs increased significantly during storage time for consecutive weeks to the amount of GSH. The levels of 2,3-DPG decreased with increasing storage time. Conclusions: Overall, The study suggest that glutathione monoethyl ester is effective to reduce the oxidative stress and the quality of RBCs can be improved.